Human T Lymphotropic Virus and Pulmonary Diseases - Dias, Apio R. N.; Falcão, Luiz F. M.; Falcão, Aline S. C.; Normando, Valéria M. F.; Quaresma, Juarez A. S. (Frontiers in Microbiology, 2018)
Human T lymphotropic virus type 1 (HTLV-1) is the etiological agent of HTLV-1-associated myelopathy, and adult T cell lymphoma/leukemia (ATL/L). Pulmonary complications such as alveolitis and bronchiectasis were found in individuals who develop TSP/HAM due to chronic inflammation. These individuals showed image anomalies in CT scans and changes in pulmonary function parameters distinctive of pulmonary disease. Furthermore, infected individuals have a greater susceptibility to pulmonary tuberculosis either due to changes in the innate immune response, in asymptomatic carriers, or to an opportunistic disease linked to immunodepression, in individuals who develop ATL/L. This summary addresses the general lack of knowledge regarding the relationship between HTLV-1 and pulmonary diseases and provides direction for future work.